Is Job Involvement Enough for Achieving Job Satisfaction? The Role of Skills Use and Group Identification - Fernández-Salinero, Samuel (Int J Environ Res Public Health, 2020)
The main objective of this research is to evaluate the influence of job involvement over job satisfaction mediated through the professional skill use and moderated by group identification. The sample of the current research was composed of 420 subjects. The main results showed that job involvement was strongly related to skill use and group identification. Moreover, the interaction of job involvement and group identification is negatively related with skill use. Our results show that there is no statistically significant relationship between job involvement and job satisfaction. Furthermore, the use of skills is strongly related to job satisfaction. Lastly, we found that a strong group identification tends to harm job satisfaction values.